THE ANALYSIS OF VLOGGING-PRONUNCIATION ERROR BY THE STUDENTS OF TEGAL POLTEKKES KEMENKES NURSING PROGRAM - Hermawan, Didi; Haryanto, Haryanto (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
The purpose of the research is to analyze the error pronunciation made by students of Poltekkes Kemenkes Semarang Diploma III Nursing Study Program Tegal when the students make a vlog. Vocabularies in the nursing program are certainly different from general English. The English that the students face is related to medical vocabulary. It needs to analyze how the students sound the vocabulary when they make a vlog. A vlog is a video logging used as media for students to practice speaking. This research employed a mixed method combining qualitative and quantitative methods. The qualitative is applied to figure out the analysis of the error made by the students and the quantitative is applied to know how the percentages of the error are. The result of the study shows that several error pronunciations occurred in consonants, vowels, and diphthongs. There are 150 errors in consonants with a percentage is 22,2 and the analyses show that the students produce the sounds/Î¸/, /Ê§/, /f/, and /k/ inappropriately. Furthermore, it was found that some error pronunciations are on the sound /Éª/, /ÊŒ/, and /i/ for vowels and /ie/,/ei/, /oÊŠ/, and /ai/ for diphthong. Additionally, vlogs could be the media for students to improve their English, particularly productive skills.